Ventas marítimas y confluencia contractual - Pejovés Macedo, José Antonio (2021)
It is estimated that ships transport about 80 % of world trade; in other words, these are goods transfers carried out by maritime mode. The maritime sale is a kind of sale and is understood as a form of distance commercial exchange. Originally, its dynamism has been closely related to the fluctuations inherent to international trade because of market opening policies or the adoption of protectionist measures.It is a known fact that in maritime sales the confluence of at least four types of contracts occurs: The sales contract, the transport contract, the documentary credit contract and the cargo insurance contract. This investigation analyzes the dynamics of maritime sales with emphasis on the main contract, which is the international sales contract, and approaches the state of the art in Peru.